2019
DOI: 10.1007/s00267-019-01158-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Farmers’ Climate Change Perceptions and Adaptation Intentions: Empirical Evidence from Austria

Abstract: The lack of timely adaptation in agriculture may hamper prosperous farm developments by neglecting risks and opportunities emerging from climate change. Understanding farmers’ perceptual and socio-cognitive processes is key in order to encourage on-farm adaptation. We aim at investigating how farmers’ individual cognition on climate change and adaptation as well as socio-environmental context factors affect agricultural adaptation intention and avoidance. We build on the Model of Private Proactive Adaptation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 74 publications
5
49
1
3
Order By: Relevance
“…Как следствие, эти риски оказываются практически «неощутимыми» (в том числе некорректно интерпретируемыми), что выступает наиболее значимым препятствием на пути управления ими. Исследования в Европе в целом [21], а также в столь разных странах, как Австрия [22], Индия [23], Колумбия [24] и США [25,26], показывают, что фермеры весьма поразному воспринимают климатические риски и даже в случае корректного восприятия вовсе не обязательно демонстрируют готовность адекватно реагировать на них.…”
Section: теоретические положенияunclassified
“…Как следствие, эти риски оказываются практически «неощутимыми» (в том числе некорректно интерпретируемыми), что выступает наиболее значимым препятствием на пути управления ими. Исследования в Европе в целом [21], а также в столь разных странах, как Австрия [22], Индия [23], Колумбия [24] и США [25,26], показывают, что фермеры весьма поразному воспринимают климатические риски и даже в случае корректного восприятия вовсе не обязательно демонстрируют готовность адекватно реагировать на них.…”
Section: теоретические положенияunclassified
“…Die Ergebnisse unterstützen die quantitative Simulation regionaler Szenarien. In leitfadengestützten Interviews wird das Anpassungsverhalten von Landwirtinnen und Landwirten an die veränderten klimatischen und hydrologischen Rahmenbedingungen erhoben (Mitter et al 2019). Die Ergebnisse zeigen Möglichkeiten auf, wie Klimawandelanpassungen in den Sektoren der Region angeregt werden können.…”
Section: Inter-und Transdisziplinäre Forschungunclassified
“…However, for farmers to make adaptation decisions, they may have to perceive climate change impacts on their farming systems. Several studies in different parts of the world have shown that there is a link between farmers’ perceptions and their adaptation actions to climate change [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%